INTERNALISASI PEMBELAJARAN EKSTRAKURIKULER BACA TULIS QUR’AN DALAM MENINGKATKAN KEMAMPUAN SISWA MEMBACA AL-QUR’AN DI SMPN 22 SURABAYA - Moch Khoiruddin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
Islamic education in order to learn the Qur'an is very important and must be prioritized to improve students' abilities in learning the Qur'an, extracurricular learning is needed at SMPN 22 Surabaya. The purpose of this study includes three problem formulations: 1) To describe the internalization of extracurricular learning to read and write the Qur'an. 2) To describe what methods are used in the internalization of extracurricular learning to read and write the Qur'an. 3) To describe what supporting and inhibiting factors in the internalization of extracurricular learning to read and write the Qur'an.This research uses a qualitative approach with a case study at SMPN 22 Surabaya. Data collection utilized interview, observation, documentation, and triangulation techniques. Data analysis employed an interactive model (Miles, Huberman, and Saldana) that included data condensation, data display, and conclusion drawing. Data validity was checked by extending observations, member checking, and translation tests.The results of the study show that: (1) Internalization of extracurricular learning of reading and writing the Qur'an at SMPN 22 Surabaya. through three stages: a) Planning includes learning objectives, stages, classes, time and place of learning, learning assessment: b) Implementation includes opening, habituation, motivation, core learning, closing prayer: c) Evaluation includes volume increase tests, memorization tests (2) The method used in extracurricular learning of reading and writing the Qur'an at SMPN 22 Surabaya, namely the Qurany method which focuses on volumes 1A-1D. (3) supporting and inhibiting factors include: a) internal supporting factors include the principal, PAI teachers in charge of extracurricular activities, b) external supporting factors include teaching ustad and parents of students. c) inhibiting factors include students lacking discipline, lack of student awareness in participating in learning.